Low body mass index adversely affects the live birth rate following fresh embryo transfer in Chinese women with polycystic ovary syndrome: a pilot study - Su, Nianjun; Wang, Lijing; Zhou, Ruiqiong; Liao, Yang; Huang, Juan; Huang, Cuiyu; Yao, Yangcheng; Qi, Quan; Huang, Li; Zhang, Xiqian; Liu, Fenghua (Frontiers in Endocrinology, 2025)
ObjectiveTo examine the relationship between body mass index (BMI) and pregnancy outcomes after fresh embryo transfer in patients with polycystic ovary syndrome (PCOS).MethodsWomen diagnosed with PCOS who underwent in vitro fertilization or intracytoplasmic sperm injection treatment at the Reproductive Center of Guangdong Maternal and Child Health Hospital in China between August 2014 and July 2023 were included. Patients were divided into four groups based on BMI: Low <18.5Kg/m2 (group 1); Normal 18.5≤BMI <24 Kg/m2(group 2); Overweight 24≤BMI <28 Kg/m2(group 3); Obesity ≥28 Kg/m2(group 4). The retrospective cohort study explored the relationship between BMI and pregnancy outcomes using a logistic regression approach. The live birth rates of different BMI groups were compared after adjusting for age, antimullerian hormone (AMH), antral follicle count (AFC), homeostatic model assessment of insulin resistance (HOMA), estrogen (E2), total testosterone (T), baseline follicle-stimulating hormone (bFSH), and baseline luteinizing hormone (bLH).ResultsA total of 649 patients with PCOS who underwent fresh embryo transfer were included. A curvilinear relationship was observed between BMI and pregnancy outcomes. Compared with the normal BMI group, the low BMI group had the lowest live birth rate (P = 0.021). An inflection point was identified at approximately 22 kg/m². When BMI was below 22 kg/m², the live birth rate increased by 29% for each 1 kg/m² increase in BMI (P = 0.018). When BMI exceeded 22 kg/m², the live birth rate plateaued. A significant interaction between age and BMI was also observed in relation to live birth rate (P = 0.011), with the adverse effect of low BMI being particularly pronounced in younger patients.ConclusionAmong patients with PCOS, those with low BMI had the lowest live birth rate following fresh embryo transfer. The optimal BMI associated with the highest live birth rate was approximately 22 kg/m².